Electrochemical and SEM Studies of Tetra-Ammine Platinum (II) [Pt(NH₃)₄](OH)₂ Solution - Jeffrey Basirun, Wan (Malaysian Journal of Science, 2002)
Electrochemical studies include cyclic voltammetry with microelectrodes were done on a solution of tetra-ammine platinum (II) [Pt(NH_3)_4](OH)_2 at pH 13 and showed that the electrochemical reduction of this compound was no different from the tetra-ammine platinm (II) [Pt(NH_3)_4](HPO_4) at pH 10.4. The solution was instable to high temperatures and results have shown that electroplating can be done at a limited temperature range for longer periods of time or at higher temperatures for short periods of time. Scanning Electron Microscopy was done on some of the constant current electrodeposited samples at high temperatures and result obtained was satisfactory.